Nudix‐type RNA pyrophosphohydrolase provides homeostasis of virulence factor pyocyanin and functions as a global regulator in Pseudomonas aeruginosa. Issue 3 (12th September 2017) - Kujawa, Martyna; Lirski, Maciej; Ziecina, Mateusz; Drabinska, Joanna; Modzelan, Marta; Kraszewska, Elzbieta
Summary: The PA0336 protein from Pseudomonas aeruginosa belongs to the family of widely distributed Nudix pyrophosphohydrolases, which catalyze the hydrolysis of pyrophosphate bonds in a variety of nucleoside diphosphate derivatives. The amino acid sequence of the PA0336 protein is highly similar to that of the RppH Nudix RNA pyrophosphohydrolase from Escherichia coli, which removes pyrophosphate from 5′‐end of triphosphorylated RNA transcripts. Trans‐complementation experiments showed that the P. aeruginosa enzyme can functionally substitute for RppH in E. coli cells indicating that, similar to RppH, the Pseudomonas hydrolase mediates RNA turnover in vivo . In order to elucidate the biological significance of the PA0336 protein in Pseudomonas cells, a PA0336 mutant strain was constructed. The mutated strain considerably increased level of the virulence factor pyocyanin compared to wild type, suggesting that PA0336 could be involved in downregulation of P. aeruginosa pathogenicity. This phenotype was reversed by complementation with the wild type but not catalytically inactive PA0336, indicating that the catalytic activity was indispensable for its biological function. Pathogenesis tests in Caenorhabditis elegans showed that the PA0336 mutant of P. aeruginosa was significantly more virulent than the parental strain, confirming further that the P. aeruginosa RNA pyrophosphohydrolase PA0336 modulates bacterial pathogenesis by down‐regulating production of virulence‐associated factors. To study the role of PA0336 further, transcriptomes of the PA0336 mutant and the wild‐type strain were compared using RNA sequencing. The level of 537 transcripts coding for proteins involved in a variety of cellular processes such as replication, transcription, translation, central metabolism and pathogenesis, was affected by the lack of PA0336. These results indicate that the PA0336 RNA pyrophosphohydrolase functions as a global regulator that influences many of transcripts including those involved in P. aeruginosa virulence. Abstract : Almost half of the proteins encoded by P. aeruginosa genome is not yet characterized; thus, a variety of pathogenesis‐associated factors may not be recognized. We are focusing on a search of novel virulence components among highly conserved Nudix proteins. Here, we show that the Nudix‐like RNA pyrophosphohydrolase RppH of P. aeruginosa modulates bacterial pathogenesis by downregulating production of virulence‐associated factors.